Circulating levels of insulin-like growth factor-II/mannose-6-phosphate receptor in obesity and type 2 diabetes. - Jeyaratnaganthan, N; Højlund, K; Kroustrup, J; Larsen, J; Bjerre, M; Levin, K; Beck-Nielsen, H; Frago, S; Hassan, A; Flyvbjerg, A; Frystyk, J (2010)
OBJECTIVE: The extracellular domain of the insulin-like growth factor II/mannose-6-phosphate receptor (IGF-II/M6P-R) is present in the circulation, but its relationship with plasma IGF-II is largely unknown. As IGF-II appears to be nutritionally regulated, we studied the impact of obesity, type 2 diabetes (T2D) and weight loss on circulating levels of IGF-II and its soluble receptor. METHODS: Twenty-three morbidly obese non-diabetic subjects were studied before and after gastric banding (GB), reducing their BMI from 59.3+/-1.8 to 52.7+/-1.6 kg/m(2). Lean controls (n=10, BMI 24.2+/-0.5 kg/m(2)), moderately obese controls (n=21, BMI 31.8+/-1.0 kg/m(2)) and obese T2D patients (n=20, BMI 32.3+/-0.8 kg/m(2)) were studied before and after a hyperinsulinaemic euglycaemic clamp. RESULTS: Morbidly obese subjects had elevated IGF-II/M6P-R and IGF-II levels, which both decreased following GB (IGF-II/M6P-R: from 0.97+/-0.038 to 0.87+/-0.030 nmol/l, P=0.001; IGF-II: from 134+/-7 to 125+/-6 nmol/l, P=0.01), as did fasting plasma glucose and insulin (P<0.05). However, the metabolic parameters correlated with neither IGF-II nor IGF-II/M6P-R. Obese diabetics had increased IGF-II/M6P-R as compared with lean and obese controls (0.82+/-0.031 vs. 0.70+/-0.033 vs. 0.74+/-0.026 nmol/l; P<0.03) and levels were unaffected by clamp. In the latter cohort, IGF-II/M6P-R but not IGF-II correlated with HbA1c, and fasting plasma C-peptide, insulin and glucose (0.34